El maltrato habitual contra la mujer y la familia en el sector sur del cantón Arenillas de la provincia de El Oro en el periodo 2010. - Moreno Romero, Julay Carolina (2015)
Through the thesis will be achieved establish the prevention of family violence and the impact of legislation, through the use of techniques and methods discrimination against women violates the principles of equal rights and respect human dignity, which hinders the participation of women on equal terms with men in all aspects of your life.